KINERJA PEGAWAI DALAM PELAYANAN ADMINISTRASI DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA MAKASSAR - Syarifuddin, Amalia; Ma'ruf, Adnan; Yusuf, Muhammad (Universitas Muhammadiyah Makassar, 2022)
ABSTRACTThe purpose of this study was to find out how the performance of employees in administrative services at the Makassar City Population and Civil Registration Office. This study used qualitative research methods. Data were collected by interviews, documentation and observation. The results of this study showed that the quality of employee performance in preventing illegal fees had been successful by installing CCTV so that the illegal extortion process did not occur. The quantity in employee performance with the number of completed activities had been successful through service standards at the Makassar City Population and Civil Registration Office. Punctuality in employee performance was quite good through the one day service program with a speed of service of less than 30 minutes and 3 working days. Effectiveness in employee performance had been successful with queue monitoring technology to facilitate the community in the service process.The Independence in employee performance had been successful through the counter service system that according to their respective duties and functions.Keywords: Performance, Administrative Services